Preparation process and application of high-elongation anti-fatigue aluminum alloy plate
Aluminum alloy sheets are prepared through specific processes and components, using the interaction of elements such as manganese and magnesium and the alumina loaded with ethylene-propylene rubber particles in the treatment solution, which solves the high energy consumption and insufficient fatigue resistance of traditional aluminum alloys during heat treatment. The problem is that high extension and good fatigue resistance are achieved.
Patent Information
- Application Number
- CN202411694504.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-25
AI Technical Summary
Traditional aluminum alloys consume high energy during heat treatment and are difficult to evenly distribute structure and stress, resulting in local stress concentration and deformation; their elongation and fatigue resistance are insufficient, making it difficult to cope with dynamic loads and frequent collisions under complex road conditions.
Aluminum alloy sheets are prepared through specific processes and ingredients, and elements such as manganese and magnesium interact with rare earth elements to form intermetallic compounds to improve strength and toughness; alumina loaded with ethylene-propylene rubber particles is introduced using treatment liquid, and the components are evenly dispersed by ultrasonic treatment , form multi-layer protection to further improve fatigue resistance.
It significantly improves the strength, toughness and fatigue resistance of aluminum alloy sheets, reduces stress concentration and fatigue cracks, and is suitable for automotive doors, hoods and fenders.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aluminum alloy plates, and relates to a preparation process and application of a high-elongation fatigue-resistant aluminum alloy plate. Background Art
[0002] With the increasingly stringent requirements for environmental protection and energy conservation, the market's requirements for the performance of automobile manufacturing materials are constantly increasing. Aluminum alloy has become an ideal material choice for lightweight automobiles due to its low density.
[0003] Traditional aluminum alloys are mainly treated by heat treatment to form a strengthening phase in the alloy matrix, thereby significantly improving the strength, hardness and other properties of the aluminum alloy. However, the heat treatment process requires high energy consumption and a long time. In addition, in the manufacture of certain complex-shaped automotive parts, the internal structure and stress state of the material will change during the heat treatment process. This change is difficult to distribute evenly, which can easily cause local stress concentration and lead to component deformation. In addition, the elongation and fatigue resistance of some aluminum alloys are not sufficient to cope with the dynamic loads and frequent collisions that vehicles undergo under various complex road conditions. They are prone to fracture under strong or long-term repeated stress, affecting the vehicle's appearance, service life and the personal safety of passengers. Summary of the invention
[0004] The purpose of the present invention is to provide a preparation process and application of a high-elongation fatigue-resistant aluminum alloy plate. The present invention prepares the aluminum alloy plate through a specific process and composition, and elements such as manganese and magnesium interact with rare earth elements to improve the strength, toughness, fatigue resistance, etc. of the alloy; and in the preparation process, a treatment liquid is used to introduce alumina loaded with EPDM rubber particles, and ultrasonic treatment is used to evenly disperse the components of the treatment liquid, which contact the surface of the ingot to form a multi-layer protection, thereby further improving the strength and fatigue resistance of the alloy.
[0005] The purpose of the present invention can be achieved by the following technical solutions: A preparation process of a high elongation fatigue-resistant aluminum alloy plate, the preparation process comprising the following steps: (1) After the raw materials are prepared, they are melted, stirred, refined, and kept warm in a smelting furnace, poured into a mold for casting, and an ingot is obtained; (2) homogenizing the ingot and cooling it in the furnace to obtain a cooled ingot; (3) sandblasting the cooled ingot and preheating it, immersing it in a treatment solution, ultrasonically treating it, and rinsing it with deionized water for 3 times to obtain a treated ingot; (4) The treated ingot is milled and hot-rolled to obtain a plate, which is then cooled to room temperature and cold-rolled and stretched to obtain a high-elongation, fatigue-resistant aluminum alloy plate.
[0006] Furthermore, the raw materials in step (1) include, by weight percentage, 3-5wt% magnesium, 0.63-0.68wt% manganese, 0.18-0.24wt% iron, 0.12-0.2wt% silicon, 0.05-0.5wt% scandium, 0.5-1.2wt% ytterbium and the balance aluminum.
[0007] Furthermore, the melting temperature of step (1) is 745-765°C; the refining agent selected for refining is hexachloroethane in an amount of 0.1-0.26wt% of the total mass of the raw materials, and argon is introduced for degassing during refining for 10-30min; the insulation temperature and time are 720-730°C and 20-30min respectively; and the casting temperature is 700-720°C.
[0008] Furthermore, the homogenization treatment in step (2) refers to placing the ingot in a heat treatment furnace, heating it to 500-550°C at a rate of 5-10°C / min, maintaining the temperature for 10-14h, and obtaining the ingot after homogenization treatment; the cooling rate of the furnace cooling is controlled at 5-10°C / min.
[0009] Furthermore, the preparation steps of the treatment solution in step (3) are: Sodium molybdate and benzotriazole are added to deionized water, stirred at 400-500 rpm for 40-50 min, then modified alumina with an average particle size of 40-60 nm is added, the speed is increased to 600-800 rpm, stirred for 1-2 h, then polyvinyl alcohol and OP-10 are added, stirring is continued for 30-40 min, the ultrasonic power is set to 100-200 W, the ultrasonic frequency is set to 10-30 kHz, the ultrasonic is applied for 20-30 min, and the treated liquid is obtained by filtering through a 0.22 μm filter membrane.
[0010] Furthermore, in parts by weight, the ratio of sodium molybdate, benzotriazole, modified alumina with an average particle size of 40-60 nm, polyvinyl alcohol, OP-10 and deionized water in the treatment solution is 0.4-0.6:0.25-0.35:0.8-1.3:0.042-0.054:0.1-0.2:18-24.
[0011] Furthermore, the modified alumina is alumina loaded with EPDM rubber particles, and the preparation steps of the alumina loaded with EPDM rubber particles are as follows: A1. Add 15-25 wt% ammonia water to a 0.4-0.6 mol / L aluminum nitrate solution, adjust the pH to 8.5-9.5, and stir until a precipitate is formed to obtain a precursor solution. A2, polystyrene microspheres and ethanol are mixed to obtain a polystyrene microsphere solution with a mass concentration of 8-12%, the polystyrene microsphere solution and the precursor solution are mixed in a volume ratio of 1:1, stirred for 1-3 hours, and the obtained mixed solution is dried in an oven at 80°C for 6-12 hours, and then treated in a muffle furnace at 450-550°C for 2-4 hours to obtain mesoporous alumina; A3. After mixing 1.2-3 parts by weight of mesoporous alumina and 6-12 parts by weight of anhydrous ethanol, add 0.3-0.7 parts by weight of ethylene-propylene rubber particles with an average particle size of 20-40 nm, set the ultrasonic power to 300-500 W, the ultrasonic frequency to 50-60 kHz, ultrasonicate for 20-40 min, stir for 1-2 h, wash with anhydrous ethanol, extract for 72 h, and dry to obtain alumina loaded with ethylene-propylene rubber particles.
[0012] Furthermore, in step (3), the pressure of the sandblasting treatment is 0.2-0.4 MPa; the temperature of the preheating treatment is 50-80°C; and the parameters of the ultrasonic treatment are: ultrasonic power is 200-400 W, ultrasonic frequency is 25-35 kHz, ultrasonic temperature is 38-42°C, and ultrasonic time is 15-35 min.
[0013] Furthermore, in step (4), the milling depth is controlled at 2-3 mm; in the hot rolling step, the milled ingot is heated to 370-420° C., the hot rolling pressure is controlled to be 12-14% each time, 4-8 times in total, the hot rolling time for each time is 0.5-1.5 min, and the hot rolling speed is 8-9 m / min; the cold rolling adopts a four-roll cold rolling mill, the surface hardness of the rolling roll is HRC60, the cold rolling pressure is controlled to be 8-9% each time, 3-5 times in total, the cold rolling time for each time is 1.5-2.5 min, and the cold rolling speed is controlled to be 4-4.4 m / min; the parameters of the stretching step are: the stretching temperature is 175-195° C., and the stretching speed is 1.5-1.7 mm / min.
[0014] Furthermore, the aluminum alloy sheet is applied to automobile doors, automobile hoods, and automobile front and rear fenders.
[0015] Beneficial effects of the present invention: (1) The present invention prepares an aluminum alloy plate through a specific process and composition, in which elements such as manganese and magnesium interact with rare earth elements to form intermetallic compounds, which further improves the strength and toughness of the alloy. At the same time, the grains are refined to reduce grain boundary stress concentration, thereby improving the fatigue resistance of the alloy.
[0016] (2) The present invention uses a treatment liquid in the preparation process, and introduces alumina loaded with EPDM particles to fill the surface of the ingot. The EPDM particles have good elasticity and toughness. When the alloy is subjected to external force, they deform and absorb part of the energy, thereby reducing stress concentration, reducing the generation and expansion of fatigue cracks, and improving the toughness and fatigue resistance of the alloy. Alumina itself has a high hardness and can be deposited on the surface of the ingot to form a physical barrier. The molybdenum ions in sodium molybdate react with oxygen in the air on the surface of the ingot to form a dense molybdenum oxide film. Benzotriazole molecules can form a stable complex with the metal ions on the surface of the aluminum alloy and adsorb on the surface of the ingot. At the same time, with the help of ultrasonic treatment, the uniformly dispersed treatment liquid components can better contact with the surface of the ingot, thereby forming a multi-layer protection, further improving the strength of the alloy, and thus improving the fatigue resistance of the alloy. DETAILED DESCRIPTION
[0017] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0018] Example 1 The preparation process of the high elongation fatigue-resistant aluminum alloy plate comprises the following steps: (1) After the raw materials are prepared, they are melted, stirred, refined, and kept warm in a smelting furnace, poured into a mold for casting, and an ingot is obtained; (2) homogenizing the ingot and cooling it in the furnace to obtain a cooled ingot; (3) sandblasting the cooled ingot and preheating it, immersing it in a treatment solution, ultrasonically treating it, and rinsing it with deionized water for 3 times to obtain a treated ingot; (4) The treated ingot is milled and hot-rolled to obtain a plate, which is then cooled to room temperature and cold-rolled and stretched to obtain a high-elongation, fatigue-resistant aluminum alloy plate.
[0019] The raw materials in step (1) of this embodiment include, by weight percentage, 3 wt % magnesium, 0.63 wt % manganese, 0.18 wt % iron, 0.12 wt % silicon, 0.05 wt % scandium, 0.5 wt % ytterbium and the balance aluminum.
[0020] In step (1), the melting temperature of this embodiment is 745° C.; the refining agent selected for refining is hexachloroethane in an amount of 0.1 wt % of the total mass of the raw materials, and argon gas is introduced for degassing during refining for 10 min; the insulation temperature and time are 720° C. and 20 min, respectively; and the casting temperature is 700° C.
[0021] In step (2), the homogenization treatment of this embodiment refers to placing the ingot in a heat treatment furnace, heating it to 500°C at a rate of 5°C / min, maintaining the temperature unchanged for 10 hours, and obtaining the ingot after homogenization treatment; the cooling rate of the furnace cooling is controlled at 5°C / min.
[0022] The steps for preparing the treatment solution in step (3) of this embodiment are: Sodium molybdate and benzotriazole were added to deionized water, stirred at 400 rpm for 40 min, and then modified alumina with an average particle size of 40 nm was added, the speed was increased to 600 rpm, and stirred for 1 h. Polyvinyl alcohol and OP-10 were added, and stirring was continued for 30 min. The ultrasonic power was set to 100 W and the ultrasonic frequency to 10 kHz. Ultrasonication was performed for 20 min, and the treated liquid was obtained by filtering through a 0.22 μm filter membrane.
[0023] In parts by weight, the ratio of sodium molybdate, benzotriazole, modified alumina with an average particle size of 40 nm, polyvinyl alcohol, OP-10 and deionized water in the treatment solution of this embodiment is 0.4:0.25:0.8:0.042:0.1:18.
[0024] The modified alumina in this embodiment is alumina loaded with EPDM rubber particles. The preparation steps of alumina loaded with EPDM rubber particles are as follows: A1. Add 15 wt % ammonia water to a 0.4 mol / L aluminum nitrate solution to adjust the pH to 8.5, and stir until a precipitate is formed to obtain a precursor solution. A2, polystyrene microspheres and ethanol were mixed to obtain a polystyrene microsphere solution with a mass concentration of 8%, the polystyrene microsphere solution and the precursor solution were mixed in a volume ratio of 1:1, stirred for 1 hour, and the obtained mixed solution was dried in an oven at 80°C for 6 hours, and then treated in a muffle furnace at 450°C for 2 hours to obtain mesoporous alumina; A3. Mix 1.2 parts by weight of mesoporous alumina and 6 parts by weight of anhydrous ethanol, add 0.3 parts by weight of ethylene-propylene rubber particles with an average particle size of 20 nm, set the ultrasonic power to 300 W, the ultrasonic frequency to 50 kHz, ultrasonicate for 20 minutes, stir for 1 hour, wash with anhydrous ethanol, extract for 72 hours, and dry to obtain alumina loaded with ethylene-propylene rubber particles.
[0025] In step (3), the pressure of the sandblasting treatment in this embodiment is 0.2 MPa; the temperature of the preheating treatment is 50°C; the parameters of the ultrasonic treatment are: ultrasonic power is 200 W, ultrasonic frequency is 25 kHz, ultrasonic temperature is 38°C, and ultrasonic time is 15 min.
[0026] In step (4), the milling depth of the present embodiment is controlled at 2 mm; in the hot rolling step, the ingot after milling is heated to 370° C., and the hot rolling pressure is controlled to be 12% each time, for a total of 4 passes, the hot rolling time for each pass is 0.5 min, and the hot rolling speed is 8 m / min; the cold rolling adopts a four-roll cold rolling mill, the surface hardness of the rolling roll is HRC60, the cold rolling pressure is controlled to be 8% each time, for a total of 3 passes, the cold rolling time for each pass is 1.5 min, and the cold rolling speed is controlled at 4 m / min; the parameters of the stretching step are: the stretching temperature is 175° C., and the stretching speed is 1.5 mm / min.
[0027] The aluminum alloy sheet of this embodiment is applied to automobile doors, automobile hoods, and automobile front and rear fenders.
[0028] Example 2 The preparation process of the high elongation fatigue-resistant aluminum alloy plate comprises the following steps: (1) After the raw materials are prepared, they are melted, stirred, refined, and kept warm in a smelting furnace, poured into a mold for casting, and an ingot is obtained; (2) homogenizing the ingot and cooling it in the furnace to obtain a cooled ingot; (3) sandblasting the cooled ingot and preheating it, immersing it in a treatment solution, ultrasonically treating it, and rinsing it with deionized water for 3 times to obtain a treated ingot; (4) The treated ingot is milled and hot-rolled to obtain a plate, which is then cooled to room temperature and cold-rolled and stretched to obtain a high-elongation, fatigue-resistant aluminum alloy plate.
[0029] The raw materials in step (1) of this embodiment include, by weight percentage, 5 wt % magnesium, 0.68 wt % manganese, 0.24 wt % iron, 0.2 wt % silicon, 0.5 wt % scandium, 1.2 wt % ytterbium and the balance aluminum.
[0030] In step (1) of this embodiment, the melting temperature is 765° C.; the refining agent selected for refining is hexachloroethane in an amount of 0.26 wt % of the total mass of the raw materials, and argon gas is introduced for degassing during refining for 30 min; the insulation temperature and time are 730° C. and 30 min, respectively; and the casting temperature is 720° C.
[0031] In step (2), the homogenization treatment of this embodiment refers to placing the ingot in a heat treatment furnace, heating it to 550°C at a rate of 10°C / min, maintaining the temperature unchanged for 14 hours, and obtaining the ingot after homogenization treatment; the cooling rate of the furnace cooling is controlled at 10°C / min.
[0032] In step (3), the steps for preparing the treatment solution of this embodiment are: Sodium molybdate and benzotriazole were added to deionized water, stirred at 500 rpm for 50 min, and then modified alumina with an average particle size of 60 mm was added, the speed was increased to 800 rpm, and stirred for 2 h. Polyvinyl alcohol and OP-10 were added, and stirring was continued for 40 min. The ultrasonic power was set to 100-200 W and the ultrasonic frequency to 30 kHz. Ultrasonication was performed for 30 min, and the treated liquid was obtained by filtering through a 0.22 μm filter membrane.
[0033] In parts by weight, the ratio of sodium molybdate, benzotriazole, modified alumina with an average particle size of 60 nm, polyvinyl alcohol, OP-10 and deionized water in the treatment solution of this embodiment is 0.6:0.35:1.3:0.054:0.2:24.
[0034] The modified alumina in this embodiment is alumina loaded with EPDM rubber particles. The preparation steps of alumina loaded with EPDM rubber particles are as follows: A1. Add 5 wt% ammonia water to a 0.6 mol / L aluminum nitrate solution to adjust the pH to 9.5, and stir until a precipitate is formed to obtain a precursor solution; A2, polystyrene microspheres and ethanol were mixed to obtain a polystyrene microsphere solution with a mass concentration of 12%, the polystyrene microsphere solution and the precursor solution were mixed in a volume ratio of 1:1, stirred for 3 hours, and the obtained mixed solution was dried in an oven at 80°C for 12 hours, and then treated in a muffle furnace at 550°C for 4 hours to obtain mesoporous alumina; A3. Mix 3 parts by weight of mesoporous alumina and 12 parts by weight of anhydrous ethanol, add 0.7 parts by weight of ethylene-propylene rubber particles with an average particle size of 40 nm, set the ultrasonic power to 500 W, the ultrasonic frequency to 60 kHz, ultrasonicate for 40 minutes, stir for 2 hours, wash with anhydrous ethanol, extract for 72 hours, and dry to obtain alumina loaded with ethylene-propylene rubber particles.
[0035] In step (3), the pressure of the sandblasting treatment in this embodiment is 0.4 MPa; the temperature of the preheating treatment is 80°C; the parameters of the ultrasonic treatment are: ultrasonic power is 400 W, ultrasonic frequency is 35 kHz, ultrasonic temperature is 42°C, and ultrasonic time is 35 min.
[0036] In step (4), the milling depth of the present embodiment is controlled at 3 mm; in the hot rolling step, the ingot after milling is heated to 420°C, and the hot rolling pressure is controlled to be 14% each time, for a total of 8 passes, the hot rolling time for each pass is 1.5 min, and the hot rolling speed is 9 m / min; the cold rolling adopts a four-roll cold rolling mill, the surface hardness of the rolling roll is HRC60, the cold rolling pressure is controlled to be 9% each time, for a total of 5 passes, the cold rolling time for each pass is 2.5 min, and the cold rolling speed is controlled at 4.4 m / min; the parameters of the stretching step are: the stretching temperature is 195°C, and the stretching speed is 1.7 mm / min.
[0037] The aluminum alloy sheet of this embodiment is applied to automobile doors, automobile hoods, and automobile front and rear fenders.
[0038] Example 3 The preparation process of the high elongation fatigue-resistant aluminum alloy plate comprises the following steps: (1) After the raw materials are prepared, they are melted, stirred, refined, and kept warm in a smelting furnace, poured into a mold for casting, and an ingot is obtained; (2) homogenizing the ingot and cooling it in the furnace to obtain a cooled ingot; (3) sandblasting the cooled ingot and preheating it, immersing it in a treatment solution, ultrasonically treating it, and rinsing it with deionized water for 3 times to obtain a treated ingot; (4) The treated ingot is milled and hot-rolled to obtain a plate, which is then cooled to room temperature and cold-rolled and stretched to obtain a high-elongation, fatigue-resistant aluminum alloy plate.
[0039] The raw materials in step (1) of this embodiment include, by weight percentage, 4 wt % magnesium, 0.655 wt % manganese, 0.21 wt % iron, 0.16 wt % silicon, 0.275 wt % scandium, 0.85 wt % ytterbium and the balance aluminum.
[0040] In step (1) of this embodiment, the melting temperature is 755° C.; the refining agent selected for refining is hexachloroethane in an amount of 0.18 wt % of the total mass of the raw materials, and argon gas is introduced for degassing during refining for 20 min; the insulation temperature and time are 725° C. and 25 min, respectively; and the casting temperature is 710° C.
[0041] In step (2), the homogenization treatment of this embodiment refers to placing the ingot in a heat treatment furnace, heating it to 525°C at a rate of 7.5°C / min, maintaining the temperature unchanged for 12 hours, and obtaining the ingot after homogenization treatment; the cooling rate of the furnace cooling is controlled at 7.5°C / min.
[0042] In step (3), the steps for preparing the treatment solution of this embodiment are: Sodium molybdate and benzotriazole were added to deionized water, stirred at 450 rpm for 45 min, and then modified alumina with an average particle size of 50 nm was added, the speed was increased to 700 rpm, and stirred for 1.5 h. Polyvinyl alcohol and OP-10 were added, and stirring was continued for 35 min. The ultrasonic power was set to 150 W and the ultrasonic frequency to 20 kHz. Ultrasonication was performed for 25 min, and the treated liquid was obtained by filtering through a 0.22 μm filter membrane.
[0043] In parts by weight, the ratio of sodium molybdate, benzotriazole, modified alumina with an average particle size of 50 nm, polyvinyl alcohol, OP-10 and deionized water in the treatment solution of this embodiment is 0.5:0.3:1.05:0.048:0.15:21.
[0044] The modified alumina in this embodiment is alumina loaded with EPDM rubber particles. The preparation steps of alumina loaded with EPDM rubber particles are as follows: A1. Add 20 wt % ammonia water to a 0.5 mol / L aluminum nitrate solution to adjust the pH to 9, and stir until a precipitate is formed to obtain a precursor solution; A2, polystyrene microspheres and ethanol are mixed to obtain a polystyrene microsphere solution with a mass concentration of 10%, the polystyrene microsphere solution and the precursor solution are mixed in a volume ratio of 1:1, stirred for 2 hours, and the obtained mixed solution is dried in an oven at 80°C for 9 hours, and then treated in a muffle furnace at 500°C for 3 hours to obtain mesoporous alumina; A3. Mix 2.1 parts by weight of mesoporous alumina and 9 parts by weight of anhydrous ethanol, add 0.5 parts by weight of ethylene-propylene rubber particles with an average particle size of 30 nm, set the ultrasonic power to 400 W, the ultrasonic frequency to 55 kHz, ultrasonicate for 30 minutes, stir for 1.5 hours, wash with anhydrous ethanol, extract for 72 hours, and dry to obtain alumina loaded with ethylene-propylene rubber particles.
[0045] In step (3), the pressure of the sandblasting treatment in this embodiment is 0.3 MPa; the temperature of the preheating treatment is 75°C; the parameters of the ultrasonic treatment are: ultrasonic power is 300 W, ultrasonic frequency is 30 kHz, ultrasonic temperature is 40°C, and ultrasonic time is 25 min.
[0046] In step (4), the milling depth of the present embodiment is controlled at 2.5 mm; in the hot rolling step, the ingot after milling is heated to 395° C., and the hot rolling pressure is controlled to be 13% each time, for a total of 68 passes, the hot rolling time for each pass is 1 min, and the hot rolling speed is 8.5 m / min; the cold rolling adopts a four-roll cold rolling mill, the surface hardness of the rolling roll is HRC60, the cold rolling pressure is controlled to be 8.5% each time, for a total of 4 passes, the cold rolling time for each pass is 2 min, and the cold rolling speed is controlled at 4.2 m / min; the parameters of the stretching step are: the stretching temperature is 185° C., and the stretching speed is 1.6 mm / min.
[0047] The aluminum alloy sheet of this embodiment is applied to automobile doors, automobile hoods, and automobile front and rear fenders.
[0048] Comparative Example 1 On the basis of Example 3, keeping other conditions the same, step (3) is changed to: immersing the cooled ingot in a treatment solution, ultrasonically treating it, and rinsing it with deionized water for 3 times to obtain a treated ingot.
[0049] Comparative Example 2 On the basis of Example 3, keeping other conditions the same, step (3) is changed to: sandblasting the cooled ingot and preheating it, immersing it in the treatment liquid for 25 minutes, and rinsing it with deionized water for 3 times to obtain a treated ingot.
[0050] Comparative Example 3 Based on Example 3, step (3) was removed and other conditions were the same as those in Example 3.
[0051] Comparative Example 4 On the basis of Example 3, the aluminum oxide in the treatment liquid is not subjected to loading treatment, and other conditions are consistent with those in Example 3.
[0052] The aluminum alloy plates prepared in Examples 1-3 and Comparative Examples 1-4 were used as samples, and the elongation of the samples was tested according to GB / T228.1-2010. The aluminum alloy plates were tested according to ASTM G 47 to determine whether stress corrosion cracking occurred within 30 days under a stress of 250 MPa. The test results are shown in Table 1 below.
[0053] Table 1
[0054] As can be seen from Table 1, the aluminum alloy plate prepared by the present invention has high elongation and good fatigue resistance. Comparative Example 1 removes the sandblasting step before using the treatment liquid, and Comparative Examples 2-4 all change the use or preparation of the treatment liquid. The treatment liquid used in the present invention introduces alumina loaded with EPDM rubber particles to fill the surface of the ingot. The EPDM rubber particles have good elasticity and toughness. When the alloy is subjected to external force, they deform and absorb part of the energy, thereby reducing stress concentration, reducing the generation and expansion of fatigue cracks, and improving the toughness and fatigue resistance of the alloy. Other components in the treatment liquid can adhere to the surface of the ingot to play a protective role, thereby improving the strength of the alloy, and then improving the toughness and fatigue resistance of the alloy.
[0055] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any indirect modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A process for preparing high elongation fatigue-resistant aluminum alloy sheet, characterized in that: The preparation process comprises the following steps: (1) After the raw materials are prepared, they are melted, stirred, refined, and kept warm in a smelting furnace, poured into a mold for casting, and an ingot is obtained; (2) homogenizing the ingot and cooling it in the furnace to obtain a cooled ingot; (3) sandblasting the cooled ingot and preheating it, immersing it in a treatment solution, ultrasonically treating it, and rinsing it with deionized water for 3 times to obtain a treated ingot; (4) The treated ingot is milled and hot-rolled to obtain a plate, which is then cooled to room temperature and cold-rolled and stretched to obtain a high-elongation, fatigue-resistant aluminum alloy plate.
2. The process for preparing the high elongation fatigue-resistant aluminum alloy sheet according to claim 1, characterized in that: The raw materials in step (1) include, by weight percentage, 3-5wt% magnesium, 0.63-0.68wt% manganese, 0.18-0.24wt% iron, 0.12-0.2wt% silicon, 0.05-0.5wt% scandium, 0.5-1.2wt% ytterbium and the balance aluminum.
3. The process for preparing the high elongation fatigue-resistant aluminum alloy sheet according to claim 1, characterized in that: The melting temperature of step (1) is 745-765°C; the refining agent selected for refining is hexachloroethane in an amount of 0.1-0.26wt% of the total mass of the raw material; argon is introduced for degassing during refining, and the ventilation time is 10-30min; the insulation temperature and time are 720-730°C and 20-30min respectively; and the casting temperature is 700-720°C.
4. The process for preparing the high elongation fatigue-resistant aluminum alloy sheet according to claim 1, characterized in that: The homogenization treatment in step (2) refers to placing the ingot into a heat treatment furnace, heating it to 500-550°C at a rate of 5-10°C / min, maintaining the temperature for 10-14 hours, and obtaining the ingot after homogenization treatment; the cooling rate of the furnace cooling is controlled at 5-10°C / min.
5. The process for preparing the high elongation fatigue-resistant aluminum alloy sheet according to claim 1, characterized in that: The steps for preparing the treatment solution in step (3) are as follows: Sodium molybdate and benzotriazole are added to deionized water, stirred at 400-500 rpm for 40-50 min, then modified alumina with an average particle size of 40-60 nm is added, the speed is increased to 600-800 rpm, stirred for 1-2 h, then polyvinyl alcohol and OP-10 are added, stirring is continued for 30-40 min, the ultrasonic power is set to 100-200 W, the ultrasonic frequency is set to 10-30 kHz, the ultrasonic is applied for 20-30 min, and the treated liquid is obtained by filtering through a 0.22 μm filter membrane.
6. The process for preparing the high elongation fatigue-resistant aluminum alloy sheet according to claim 5, characterized in that: In parts by weight, the ratio of sodium molybdate, benzotriazole, modified alumina with an average particle size of 40-60 nm, polyvinyl alcohol, OP-10 and deionized water in the treatment solution is 0.4-0.6:0.25-0.35:0.8-1.3:0.042-0.054:0.1-0.2:18-24.
7. The process for preparing the high elongation fatigue-resistant aluminum alloy sheet according to claim 6, characterized in that: The modified alumina is alumina loaded with EPDM rubber particles, and the preparation steps of the alumina loaded with EPDM rubber particles are as follows: A1. Add 15-25 wt% ammonia water to a 0.4-0.6 mol / L aluminum nitrate solution, adjust the pH to 8.5-9.5, and stir until a precipitate is formed to obtain a precursor solution. A2, polystyrene microspheres and ethanol are mixed to obtain a polystyrene microsphere solution with a mass concentration of 8-12%, the polystyrene microsphere solution and the precursor solution are mixed in a volume ratio of 1:1, stirred for 1-3 hours, and the obtained mixed solution is dried in an oven at 80°C for 6-12 hours, and then treated in a muffle furnace at 450-550°C for 2-4 hours to obtain mesoporous alumina; A3. After mixing 1.2-3 parts by weight of mesoporous alumina and 6-12 parts by weight of anhydrous ethanol, add 0.3-0.7 parts by weight of ethylene-propylene rubber particles with an average particle size of 20-40 nm, set the ultrasonic power to 300-500 W, the ultrasonic frequency to 50-60 kHz, ultrasonicate for 20-40 min, stir for 1-2 h, wash with anhydrous ethanol, extract for 72 h, and dry to obtain alumina loaded with ethylene-propylene rubber particles.
8. The process for preparing the high elongation fatigue-resistant aluminum alloy sheet according to claim 1, characterized in that: The pressure of the sandblasting treatment in step (3) is 0.2-0.4 MPa; the temperature of the preheating treatment is 50-80°C; the parameters of the ultrasonic treatment are: ultrasonic power is 200-400 W, ultrasonic frequency is 25-35 kHz, ultrasonic temperature is 38-42°C, and ultrasonic time is 15-35 min.
9. The process for preparing the high elongation fatigue-resistant aluminum alloy sheet according to claim 1, characterized in that: In step (4), the milling depth is controlled at 2-3 mm; in the hot rolling step, the ingot after milling is heated to 370-420° C., the hot rolling pressure is controlled to be 12-14% each time, 4-8 passes are performed in total, the hot rolling time for each pass is 0.5-1.5 min, and the hot rolling speed is 8-9 m / min; the cold rolling adopts a four-roll cold rolling mill, the surface hardness of the rolling roll is HRC60, the cold rolling pressure is controlled to be 8-9% each time, 3-5 passes are performed in total, the cold rolling time for each pass is 1.5-2.5 min, and the cold rolling speed is controlled to be 4-4.4 m / min; the parameters of the stretching step are: the stretching temperature is 175-195° C., and the stretching speed is 1.5-1.7 mm / min.
10. The high elongation fatigue-resistant aluminum alloy sheet according to claims 1 to 9, characterized in that: The aluminum alloy sheet is applied to automobile doors, automobile engine hoods, and automobile front and rear fenders.
Citation Information
Patent Citations
Corrosion-resistant magnesium aluminum alloy chromium-free passivation solution
CN104561970A
Aluminum alloy die-casting forming technology for gearbox body
CN107523706A
High-strength corrosion-resistant 7xxx series aluminum alloy plate for vehicle and preparation method of 7xxx series aluminum alloy plate
CN116463532A
High-silver light aluminum alloy and processing technology thereof
CN117187626A
Corrosion-resistant aluminum alloy profile for ships and preparation method of corrosion-resistant aluminum alloy profile
CN118308633A